Herpes oesophagitis in a healthy 8 year-old. Issue 3 (March 1987) - Lambert, H; Eastham, E J
Abstract : An 8 year-old, immunocompetent child developed a severe acute herpetic oesophagitis in the absence of oropharyngeal lesions. Intravenous treatment with the antiviral drug, acyclovir, relieved symptoms within 24 hours.